Clinical Management in Systemic Type Pseudohypoaldosteronism Due to SCNN1B Variant and Literature Review - Gülin Karacan Küçükali; Semra Çetinkaya; Gaffari Tunç; M. Melek Oğuz; Nurullah Çelik; Kardelen Yağmur Akkaş; Saliha Şenel; Naz Güleray Lafcı; Şenay Savaş Erdeve (Galenos Yayincilik, 2021)
Systemic pseudohypoaldosteronism (PHA) is a rare, salt-wasting syndrome that is caused by inactivating variants in genes encoding epithelial sodium channel subunits. Hyponatremia, hyperkalemia, metabolic acidosis, increased aldosterone and renin levels are expected findings in PHA. Clinical management is challenging due to high dose oral replacement therapy. Furthermore, patients with systemic PHA require life-long therapy. Here we report a patient with systemic PHA due to SCNN1B variant whose hyponatremia and hyperkalemia was detected at the 24th hour of life. Hyperkalemia did not improve with conventional treatments and dialysis was required. He also developed myocarditis and hypertension in follow-up. Challenges for diagnosis and treatment in this patient are discussed herein. In addition, published evidence concerning common features of patients with SCNN1B variant are reviewed.